Penguatan Profil Pelajar Pancasila melalui TPACK untuk Pemecahan Masalah Matematika SMPN - Purba, Bachti Pristian; Hasugian, Evelyn Sri Rezeki; Sidabalok, Sarah Patricia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Quality education is very important to form superior and characterful Human Resources (HR). One of the main goals of education in Indonesia is to form a Pancasila Student Profile, which is in line with Pancasila as the basis of the country. One of the challenges in education is the low mathematics learning outcomes of students in Indonesia, as reflected in the 2022 PISA survey. For this reason, innovation is needed in learning methods, one of which is through TPACK-based differentiated learning by strengthening the Pancasila Student Profile. This research aims to examine the effect of TPACK-based differentiated learning on students' mathematical problem solving abilities, as well as how strengthening the Pancasila Student Profile can support this goal. This research uses a One Group Pretest-Posttest experimental design. The research sample consisted of 31 class VIII students at SMPN 2 Girsang Sipanganbolon, Simalungun Regency, who were selected using a purposive sampling technique. Data was collected through mathematics learning outcomes tests before and after treatment, and analyzed using the Richaroon formula (2013). The results showed a significant increase in students' mathematical problem solving abilities, with an average pretest score of 70.47 and posttest 77.81. Testing for normality and homogeneity shows that the data is normally and homogeneously distributed. The t test produced a calculated t value of 28.080, which shows that TPACK-based differentiated learning by strengthening the Pancasila Student Profile is effective in improving students' mathematics learning outcomes. The implication of this research is that this learning method can be applied to improve mathematics learning outcomes while forming student character in accordance with Pancasila values.